Pengaruh Media Edukasi Video Terhadap Peningkatan Pengetahuan Dan Keterampilan Siswi Tentang Sadari Di SMP Negeri 1 Baitussalam - Adinda, Novia Restu; Kasmini, Lili; Fazlaini, Risna (Journal of Innovative and Creativity, 2026)
The study purpose was to determine the effect of video-based educational media on improving knowledge and skills of female students regarding Breast Self-Examination (BSE/SADARI) at SMP Negeri 1 Baitussalam, Aceh Besar Regency. Breast cancer remains one of the leading causes of death among women, and early detection through SADARI is an effective preventive effort, especially for adolescents. However, limited knowledge and lack of practical skills among students highlight the need for effective educational interventions using engaging media. Materials and methods. This study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest method. The research was conducted on 15 female students. Data were collected using questionnaires to measure knowledge and observation checklists to assess students’ skills in performing SADARI. The intervention was delivered through video-based educational media. Data analysis was carried out using descriptive and inferential statistics to compare pretest and posttest results. Results. The findings showed a significant improvement in both knowledge and skills after the intervention. Before the educational video was administered, most respondents had low levels of knowledge and inadequate skills. After the intervention, the majority of students demonstrated good knowledge and were able to perform SADARI correctly. The use of video media effectively enhanced students’ understanding through audio-visual presentation, making learning more engaging and easier to comprehend. Conclusions. Video-based educational media has a significant effect on improving knowledge and practical skills of female students regarding SADARI. This method is recommended as an effective health education strategy to promote early detection of breast cancer among adolescents. Keywords: video education, breast self-examination, knowledge, skills, adolescents